A 25 GHz Voltage-controlled oscillator (VCO) for automotive collision avoidance radar - Nazuhusna Khalid; N. I. M. Nor; H. Aris; M. N. H. Hashim; Selveshwaran A/L Ramesh; S. N. Supardan, (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
This paper presents the design and implementation of a 25 GHz voltage-controlled oscillator (VCO) tailored for automotive collision avoidance radar systems. The VCO, a crucial component of the synthesizer, is essential for generating variable frequencies. This study focuses on addressing the challenges of high-power consumption and phase noise, which are critical factors in the performance of radar systems. The simulations were conducted using LTspice to evaluate the VCO's performance in terms of phase noise and power consumption, utilizing 0.18 µm CMOS technology. The proposed VCO employs a modified current-reuse configuration to enhance power efficiency and incorporates resistive and inductive source degeneration techniques to minimize phase noise. The results demonstrate that the VCO achieves a tuning range of 25.34–25.94 GHz, with an impressive phase noise of -156.61 dBc/Hz at a 1 MHz offset and -157.43 dBc/Hz at a 10 MHz offset for the resistive degeneration configuration. The inductive degeneration configuration shows a phase noise of -156.562 dBc/Hz at a 1 MHz offset and -157.431 dBc/Hz at a 10 MHz offset. Additionally, the power consumption is measured at 207.4 mW for the resistive configuration and 208.39 mW for the inductive configuration. These findings indicate that the proposed VCO design meets the stringent requirements of low power consumption and low phase noise and provides a reliable solution for implementing efficient radar systems in automotive applications.